AKSES PENDIDIKAN MASYARAKAT URBAN PASCA PENERAPAN SISTEM ZONASI DI SURABAYA - Rolita Adelia Prasetya; Farid Pribadi (Jurnal Pendidikan Ilmu Sosial, 2021)
This research will discuss about access to urban community education after the Implementation of the zoning system, this study departs from the number of urban communities living on the railroad banks in Ketintang, Surabaya. The purpose of this study is to determine access to education for urban communities related to values, and patterns of action constructed by urban communities in accessing formal education from pre to post implementation of the zoning system policy. This research will be dissected using social construction theory with externalization, objectivation and internalization processes proposed by Peter L Berger with a qualitative descriptive approach. The result of this study is that access to education has turned into a zoning system, making it difficult for urban communities who have a residency status because the country's schools limit quotas and prioritize native citizens of Surabaya.